Thoracic sympathetic block reduces respiratory system compliance - Benseñor, Fábio Ely Martins; Vieira, Joaquim Edson; Auler Júnior, Jose Otávio Costa (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Thoracic epidural anesthesia (TEA) following thoracic surgery presents known analgesic and respiratory benefi ts. However, intraoperative thoracic sympathetic block may trigger airway hyperreactivity. This study weighed up these benefi cial and undesirable effects on intraoperative respiratory mechanics. DESIGN AND SETTING: Randomized, doubleblind clinical study at a tertiary public hospital. METHODS: Nineteen patients scheduled for partial lung resection were distributed using a random number table into groups receiving active TEA (15 ml 0.5% bupivacaine, n = 9) or placebo (15 ml 0.9% saline, n = 10) solutions that also contained 1:200,000 epinephrine and 2 mg morphine. Under general anesthesia, fl ows and airway and esophageal pressures were recorded. Pressure-volume curves, lower infl ection points (LIP), resistance and compliance at 10 ml/kg tidal volume were established for respiratory system, chest wall and lungs. Student’s t test was performed, including confi - dence intervals (CI). RESULTS: Bupivacaine rose 5 ± 1 dermatomes upwards and 6 ± 1 downwards. LIP was higher in the bupivacaine group (6.2 ± 2.3 versus 3.6 ± 0.6 cmH2O, p = 0.016, CI = -3.4 to -1.8). Respiratory system and lung compliance were higher in the placebo group (respectively 73.3 ± 10.6 versus 51.9 ± 15.5, p = 0.003, CI = 19.1 to 23.7; 127.2 ± 31.7 versus 70.2 ± 23.1 ml/cmH2O, p < 0.001, CI = 61 to 53). Resistance and chest wall compliance showed no difference. CONCLUSION: TEA decreased respiratory system compliance by reducing its lung component. Resistance was unaffected. Under TEA, positive end-expiratory pressure and recruitment maneuvers are advisable.